CHARACTERISTICS OF BIOMASS RESULTING FROM AGRO-INDUSTRIAL PROCESSES AND POSSIBILITIES OF ITS EVALUATION IN THE CONTEXT OF THE CIRCULAR BIOECONOMY - TAȘCA, Corina (Journal of Engineering Science (Chişinău))
Waste management in the agro-industrial sector is a significant issue that demands a thoughtful and multifaceted approach, not only to prevent environmental contamination with harmful substances but also to produce value-added products. The selection of waste treatment technology should be based on the waste's nature, composition, and initial quantities, which are determined by the primary production cycle, raw materials, and applied conditions. This study focuses on exploring innovative methods to enhancethe conversion rate and efficiency of organic waste biomass by incorporating small amounts of biologically active substances into the fermentation mix. The research also examines the impact of natural plant-based additives on various types of biomass within the agro-industrial sector. In agricultural areas where industries produce wine, spirits, beer, and juices, liquid waste is continuously produced in a state of ongoing digestion. This requires strict measures to prevent its direct disposal into landfills, water bodies, or other environmental compartments, as such actions could disrupt the natural balance of soil microorganisms, plants, and other organisms. Present-day methods for handling solid organic waste often include its application in agriculture, incineration, anaerobic digestion, composting, and related processes. Liquid waste from the agro-industrial sector can be treated through processes like sedimentation, settling, and anaerobic fermentation.